“If I Wear High Heels, I’m Gonna Be Judged”: An Exploration of Women Doctoral Students’ Experiences in STEM Conference Spaces (International Journal of Multidisciplinary Perspectives in Higher Education, 2025)
A gender gap in science, technology, engineering, and mathematics (STEM) fields persists despite the growing acknowledgment of the inequities women face. One pathway into STEM careers is attending academic conferences, where doctoral students can engage with the wider community in their field. This study shares the experiences of women doctoral students at academic conferences, using a gender and science identity lens. We conducted semi-structured interviews with 23 women doctoral students in STEM programs at a university in New Zealand. Our findings show that participants experienced conferences as gendered spaces and these experiences affected the development of their science identity in multiple ways. Our research highlights a continued need to combat gender inequities in higher education and reimagine conferences to be more inclusive. Combatting gender bias in such spaces requires changing organisational practices to enable women’s science identities to flourish.